eCM 2018
DOI: 10.22203/ecm.v035a08
|View full text |Cite
|
Sign up to set email alerts
|

Poly(trimethylene carbonate) and poly(D,L-lactic acid) modify human dendritic cell responses to staphylococci but do not affect Th1 and Th2 cell development

Abstract: Biomaterial-associated infections (BAIs) are frequent complications in the use of medical devices (biomaterials) correlated with considerable patient discomfort and high treatment costs. The presence of a biomaterial in the host causes derangement of local immune responses increasing susceptibility to infection. Dendritic cells (DCs) have an important role in directing the nature of immune responses by activating and controlling CD4 + T helper (Th) cell responses. To assess the immunomodulatory effect of the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 53 publications
0
7
0
1
Order By: Relevance
“…Likely, APCs are already impaired by the implant and contribute to the immune compromised environment and increased bacterial colonization. Two biodegradable and biocompatible materials that are known to provoke a normal foreign body response were tested for DC activation and subsequent DC-mediated T cell proliferation and polarization in the presence or absence of S. aureus and S. epidermidis , respectively (103). The authors found that the biomaterials alone did not induce DC activation and subsequent DC-mediated T cell activation, but in combination with bacteria, DCs had a slightly changed cytokine secretion profile.…”
Section: Immune Response Against Chronic Implant-related Bone Infectionsmentioning
confidence: 99%
“…Likely, APCs are already impaired by the implant and contribute to the immune compromised environment and increased bacterial colonization. Two biodegradable and biocompatible materials that are known to provoke a normal foreign body response were tested for DC activation and subsequent DC-mediated T cell proliferation and polarization in the presence or absence of S. aureus and S. epidermidis , respectively (103). The authors found that the biomaterials alone did not induce DC activation and subsequent DC-mediated T cell activation, but in combination with bacteria, DCs had a slightly changed cytokine secretion profile.…”
Section: Immune Response Against Chronic Implant-related Bone Infectionsmentioning
confidence: 99%
“…147 Another study found that biomaterials with the presence of bacteria can induce DCs to secrete cytokines, and subsequent T-cell activation is mediated by DCs. 148 Uzhviyuk et al explored the influence of GO nanoparticles on the differentiation of human DCs. 149 It was found that GO had no notable effect on the viability and percentage of DCs in the culture medium.…”
Section: Dendritic Cellsmentioning
confidence: 99%
“…Although chemical coating or surface modifications can indeed modulate DC maturation, [68,69] biomaterial-regulation of DCs has not yet shown effectiveness in altering T cell responses to Staphylococci. [39,70,71]…”
Section: Host Immune Response To Biomaterials Infectionmentioning
confidence: 99%